¡Achachay, qué frío, ve! Subjetivización de ‘ve’ como un marcador discursivo - Zambrano Ojeda, Isis Nathaly (El Colegio de México, A.C., 2023)
The traditional definition of grammaticalization assumes a notion of unidirectionally; however, studies have identified changes that present a different directionality, such as changes from verbs to discourse markers. In the Ecuadorian Quiteño variety, the expression ve there is a shift from syntax to discourse as in ¿Qué más, ve? ¡Achachay, qué frío, ve! ¡Calla, ve! Based on a corpus of 51 cases retrieved from social media, this study aims to describe the semantic and functional behavior of ve following the Subjectification criteria and to examine if it meets the characteristics of discourse markers. Through a detailed analysis, the data suggest that the particle ve reflectsthe loss of the lexical value of the verb ver and has been recategorized as aconversational discourse marker that has acquired new values in discourse.